Keller-Osserman a priori estimates and removability result for the anisotropic porous medium equation with absorption term - Shan, M.A. (Український математичний вісник, 2018)
We obtain the removability result for quasilinear equations of the special form and prove a priori estimates of the Keller–Osserman type.